Proposed Business Strategy for Milka Baby Shop - Wulandary, Aztried; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2014)
Abstract - Milka Baby Shop is a family business retail that provides a variety of children need from their born preparation phase until their growth phase. Milka Baby Shop established in January 2011 which located in Taman Galaxi Indah Residential, South Bekasi. Milka Baby Shop products were divided into several categories such as clothing, eating equipment, toiletries, toys, and so on. Milka Baby Shop also provided free gift-wrapping services for customers. Since Milka Baby Shop established in January 2011, the revenues were fluctuated as seen from its financial statement. Currently Milka Baby Shop is no longer able to survive and temporary closed since August 2013. The research began with the data collection through questionnaires, interviews, literature, and references. Then do the exploration of the problems faced by Milka Baby Shop by analyzing the external and internal factors Milka Baby Shop. External factors were analyzed using the Porterâ€™s Five Forces to determine the threat of the new entrants, bargaining power of buyers, threat of substitute products, bargaining power of suppliers, and rivalry among existing competitor. With this analysis, the threats and opportunities that faced by Milka Baby Shop is known. Then internal factors were analyzed using value chain analysis and business model canvas to know what are the strengths and weaknesses of Milka Baby Shop. Then the threats, opportunities, strengths, and weaknesses that have been known is used to formulate the appropriate strategies using diamond strategy, TOWS matrix, and proposed business model canvas. Diamond strategy showed that Milka Baby Shop should emphasize its business strategy into arena and vehicle. Then TOWS matrix generating strategies related to arena and vehicle which are establish an online shop to selling and marketing, do advertising and promotion strategy, make a good ambience in store and maintain a good service for customer, provide the baby needs completely, maintain a good relationship with suppliers, find new principal, expansion & diversification, restructuring the organization, and assets management strategy.Milka Baby Shop still has an opportunity to reset the business. At the beginning Milka Baby Shop has to control the product quality, the product variety completeness, and the products price in order to achieve their vision to become one stop shopping baby stuff.Â Keyword: Retail Business, TOWS Matrix, Business Model Canvas